Strategic Management : Kellogg Company / Aida Kartina Mohd Abd.Karim and Noorul Husna Burhannudin - Mohd Abd.Karim, Aida Kartina; Burhannudin, Noorul Husna (2007)
Corporate Social Responsibility (CSR) can be defined as a concept that organizations, especially the corporations, have an obligation to consider the interests of customers, employees, shareholders, communities, and ecological considerations in all aspects of their operations. This obligation is seen to extend beyond their statutory obligation to comply with legislation. Other definition by the World Business Council for Sustainable Development states that "Corporate social responsibility is the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as of the local community and society at large." This holistic approach to business regards organizations as (for example) being full partners in their communities, rather than seeing them more narrowly as being primarily in business to make profits and serve the needs of their shareholders